GE_GERICHTE A/1691/2022 vom 7. November 2022 - GE Cour de justice (2022)
DROIT D'ÊTRE ENTENDU;DOMICILE;PERMIS DE CONDUIRE;RECONNAISSANCE DU PERMIS;DEVOIR DE COLLABORER | Cst.29.al2; LCR.22.al1; OAC.2.al1; CC.23; LCR.42.al3bis.leta; LCR.42.al4; LCR.44.al1; LCR.45.al1